Efforts to Improve Learning Quality for Civil Study on Unity in Diversity Through the Team Game Tournament (TGT) Method in Class IV Elementary School Students - Nawiyah Nawiyah (Green Publisher Indonesia, 2023)
The purpose of the srudy are; (1) to describe the application of the Teams Games Tournament (TGT) learning model, and (2) to determine the improvement in the quality of learning through TGT Model. This research method is qualitative. It was found that 1) student test results in cycle I meeting 1 obtained an average student test result of 55.42 with a completeness percentage of 25%, cycle I meeting 2 obtained an average student test result of 63.33 with a completeness percentage of 38%, cycle II meeting 1 obtained an average student test result of 72.50 with a completeness percentage of 54%, cycle II meeting 2 obtained an average student test result of 85.83 with a completeness percentage of 100%, shows a significant increase in achievement. 2) The application of cooperative learning through TGT can improve the quality of student civic education learning outcomes. The average score of students' test results each cycle has increased. In cycle I meeting 1 obtained an average student test result of 55.42 with a completeness percentage of 25%, cycle I meeting 2 obtained an average student test result of 63.33 with a completeness percentage of 38%, cycle II meeting 1 obtained an average student test result of 72.50 with a completeness percentage of 54%, cycle II meeting 2 obtained an average student test result of 85.83 with a completeness percentage of 100%, shows a significant increase in achievement.